Facile Li-Al layered double hydroxide films on Al alloy for enhanced hydrophobicity, anti-biofouling and anti-corrosion performance. (20th July 2021) - Li, Ji; Yuan, Tianci; Zhou, Chengliang; Chen, Bo; Shuai, Yi; Wu, Dawang; Chen, Dongchu; Luo, Xiaohu; Cheng, Y.Frank; Liu, Yali
Graphical abstract: Highlights: A new anti-bacterial and anti-corrosion agent was synthesized. Multifunctional Li-Al layered double hydroxides (LDHs) films on aluminum alloy was prepared by a facile method. Significant enhanced corrosion protection property and excellent hydrophobicity property with the discussion of surface roughness. Excellent anti-bacterial property against Escherichia coli (gram-negative), Bacillus subtilis (gram-positive) and sulfate-reducing bacteria (anaerobic). Abstract: In this work, lithium (Li)-aluminum (Al) layered double hydroxide (LDH) films modified by 4-amino-2-((hydrazine methylene) amino)-4-oxobutanoic acid (denoted as AOA acid) and/or 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane were prepared on 6N01 Al alloy by a facile, in-situ growth method with enhanced hydrophobicity, anti-biofouling and anti-corrosion performance. The preparation is low energy consumptive and environment friendly, relying on self-assembly at ambient temperature. The structure, molecular weight and functional groups of the synthesized AOA acid were characterized by NMR spectrometer, ESI-MS spectrometer and Fourier transform infrared (FT-IR) spectroscopy. And the compositions, structure and morphology of the films were characterized by Fourier transform infrared (FT-IR) spectroscopy, glancing-angle X-ray diffraction (GA-XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM) and energy-dispersive x-ray spectrum (EDS). Water contact angle measurements (CA) and atomic force microscopy (AFM) characterization show that the films possess a micro/nanostructure with an improved hydrophobicity. Immersion test, neutral salt tests (NSS) and electrochemical impedance spectroscopy (EIS) conducted in 3.5 wt.% NaCl solutions demonstrate the improved corrosion resistance of the films over bare Al alloy. Meanwhile, the films also possess an excellent anti-bacterial property to Escherichia coli, Bacillus subtilis and sulfate-reducing bacteria.